2019
DOI: 10.7224/1537-2073.2019-005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in a Modern Cohort of Treated Patients with Multiple Sclerosis from Diagnosis Up to 15 Years

Abstract: Background: Before disease-modifying therapies (DMTs) were available, the natural history of multiple sclerosis (MS) regarding attainment of accepted disability milestones was reported with fairly wide variance comparing outcomes across studies. The influence of DMTs on these outcomes is unknown. This study aimed to calculate attainment of disability milestones during the first 15 years after onset of DMTtreated relapsing forms of MS (RMS). Methods: As a retrospective study, all available disability data (coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The results align with recent data reported in the literature. Scott et al, in a cohort of 184 American treated PwMS followed longitudinally for at least 14 years, demonstrated that within 10.7 years from onset, half of the patients reached an EDSS score of 3.0 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results align with recent data reported in the literature. Scott et al, in a cohort of 184 American treated PwMS followed longitudinally for at least 14 years, demonstrated that within 10.7 years from onset, half of the patients reached an EDSS score of 3.0 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results align with recent data reported in the literature. Scott et al, in a cohort of 184 American treated PwMS followed longitudinally for at least 14 years, demonstrated that within 10.7 years from onset, half of the patients reached an EDSS score of 3.0 [55]. Harari et al, in an epidemiogenetical study that spanned over 18 years and involved a cohort of 2396 Jewish PwMS (Iraqi-born Jewish patients or Israeli-born Jewish patients with both parents born in Iraq vs. those of Northern European origin, who were partially treated with DMTs), concluded that patients of Iraqi origin tended to progress faster to an EDSS of 3.0 compared to those of Northern European origin.…”
Section: Discussionmentioning
confidence: 99%